244 Point Prevalence of Frailty and Confusion Exceeds the Capacity of a Single Ward - Specialist Geriatric Wards to Lead Best Practice. (16th September 2019) - O' Donnell, Desmond; O'Mahony, Anne; O' Donoghue, Alice; McMahon, Clare; Doyle, Marie; O' Gorman, Millie; Mulcahy, Riona; Pope, George; Cooke, John
Abstract: Background: Our Model 4 Hospital will open a Specialist Geriatric Ward in the coming months. This ward will focus on the provision of evidence-based care to confused and frail older adults. Careful selection of patients who would most benefit from this care will be vital to ensure success. We aim to determine the prevalence of frailty and confusion in our inpatient cohort to determine expected demand on this new service and to inform admission criteria. Methods: All adult inpatients were screened for frailty (pre-admission status ) using the Rockwood Clinical Frailty Scale (CFS). Point prevalence of confusion (combination of pre-existing dementia and incident delirium) was calculated by measuring 4AT scores on all adult inpatients (>16 years of age), with the exclusion of obstetric, paediatric, critical care and psychiatric wards. Eleven wards were visited by a team of six experienced geriatric practitioners during a one-week period in April 2019. Results: In total, 257 patients were assessed. The median age was 74 years (16-99). The majority were male (54.9 %). 152 patients resided on a dedicated medical ward (59.1%). The point prevalence of pre-morbid frailty (CFS Score ≥ 5) was 39.9%. The point prevalence of confusion (4AT score ≥4) was 24.4%. Conclusion: Our data show that frailty and delirium are highly prevalent in hospital inpatients. It is not feasible for this number of frail and confused patients to be cohorted in a single specialist area. It is therefore important that each hospital determine admission criteria to identify those at greatest need. Clearly, given the prevalence outlined here, there will be a large number of patients likely to benefit from but unable to access a Specialist Geriatric Ward. These wards therefore need to also serve as exemplars of best practice so that evidence-based care for this vulnerable cohort can be disseminated within an institution.